Sphaerolecanium prunastri Boyer de Fonscolombe (Hemiptera: Coccidae): distribution, host plants and natural enemies in the Turkish Lake Distr ict (Bollettino di zoologia agraria e bachicoltura, 2024)
Sphaerolecanium prunastri was an economically important pest ofalmond, apricot, and sweet chen-y, sour cherry, peach and plum in the TurkishLake District (Afyon, Burdur and Isparta prov[nces lll Turkey) LO 1999-2001.Although there are numerous natural enemies of S. prunastri, it reached very highpopulation densities in Afyon. Hymenopteran parasitoids recorded were: Discodescoccophagus (Ratzeburg), Microterys hortulans Erdos, Metaphycus sp. (Hym.,Encyrtidae); Coccophagus lycimnia (Walker), Coccophagus sp., (ApheUnidae);Cerapterocerus mirabilis Westwood, Pachyneuron muscarum (Linnaeus)(Pteromalidae); Aprostocetus sp. (Eulophidae). Predators recorded were:Cybocephalus fodori minor Endrody-Younga (Col., Cybocephalidae); Chilochorusbipustulatus (L.), Exochomus quadripustulatus L. (Col., Coccinellidae); Calymmacommunirnacula (Denis & Schiffermtiller) (Lep., Noctuidae) and an unidentifiedspecies of Hemiptera (Heteroptera).
Keywords: Sphaerolecaniwn pnmastri; stone fruits; natural enemies; Turkish Lake District